Metode Forward Chaining Pada Sistem Pakar Skrining Vaksinasi Covid-19 - ABDUL AZIS (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
One of the efforts to prevent the spread of Covid-19 is vaccination. Vaccines are antigens that have been processed which when given to a person will give rise to immunity against certain infectious diseases. Vaccination triggers immunity by causing the recipient's immune system to react to the antigens contained in the coronavirus vaccine. Therefore, in the flow of Covid-19 vaccination services, the public is directed to carry out health screenings before vaccinating. Covid-19 screening is an early stage in the implementation of the Covid-19 vaccination which aims to identify and provide an overview of a person's body condition or health before getting a Covid-19 vaccination injection. One of the problems at the Arcawinangun Village Hall during the vaccination screening process was the lack of knowledge and underestimating the vaccination screening process. The vaccination screening expert system is a screening application that can assist the public in pre-diagnosing the Covid-19 vaccination screening process. The method used in building this system is Forward Chaining and the system development method is Extreme Programming. Two tests were carried out, namely black box testing and accuracy testing. Based on the tests carried out using the black box, the functionality of all menus is appropriate and in accordance with the function. Based on accuracy testing, the system can show an accuracy of 90%.